STUDI KELAYAKAN BISNIS PENGOLAHAN SUSU SAPI MURNI DALAM ASPEK PASAR DAN PEMASARAN di KUD Argopuro Krucil - Siti Aisyah; Yeni Fatur Rohmah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2024)
This research analyzes the feasibility study of pure cow's milk processing business from the market and marketing aspects, focusing on the village unit cooperative (kud) argopuro in krucil district, probolinggo regency. The problem examined is how the feasibility of the pure cow’s milk processing business managed by kud argopuro is assessed from market and marketing aspects. This study aims to determine and analyze the feasibility of the milk processing business using qualitative field research methods. The research utilizes both primary and secondary data, with data collection techniques including observation, interviews, and documentation. The results show that the availability of raw materials, strategic factory location, and growing market opportunities make the business viable. The existence of 4,079 dairy cows in krucil supports the sustainability of milk supply. The findings conclude that, based on the market and marketing aspects, the business operated by kud argopuro is feasible and has potential for further development in the future